Multilateral Official Debt Rescheduling : Recent Experience, May 1988. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1987)
This paper describes developments in multilateral official debt renegotiations over the 18 months through December 1987. The most important new departure in multilateral official debt renegotiations was the adaptation of policies by Paris Club creditors in response to the protracted problems of the poorest and most heavily indebted countries at the same time that other initiatives were launched for low-income countries, including the proposal for enhancement of the IMF's structural adjustment facility. Official creditors have generally preserved concessional interest rates in the restructuring of official development assistance (ODA) loans; moreover, for the poorest debtors, some creditors have converted such loans into grants. The question of interest concessions on other categories of debts rescheduled by the Paris Club was raised, inter alia, by the Venice summit but no consensus exists among creditors for changing the current practice. By regularly excluding short-term debt from reschedulings, debtors and creditors have also frequently succeeded in protecting the flow of short-term trade financing, which is often vital to the financing of an IMF-supported program.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet